Stringently Defined Otitis Prone Children Demonstrate Deficient Naturally Induced Mucosal Antibody Response to Moraxella catarrhalis Proteins - Ren, Dabin; Murphy, Timothy F.; Lafontaine, Eric R.; Pichichero, Michael E. (Frontiers in Immunology, 2017)
Moraxella catarrhalis (Mcat) is a prominent mucosal pathogen causing acute otitis media (AOM). We studied Mcat nasopharyngeal (NP) colonization, AOM frequency and mucosal antibody responses to four vaccine candidate Mcat proteins: outer membrane protein (OMP) CD, oligopeptide permease (Opp)A, hemagglutinin (Hag), and Pilin A clade 2 (PilA2) from stringently defined otitis prone (sOP) children, who experience the greatest burden of disease, compared to non-otitis prone (NOP) children. sOP children had higher NP colonization of Mcat (30% vs. 22%, P = 0.0003) and Mcat-caused AOM rates (49% vs. 24%, P < 0.0001) than NOP children. Natural acquisition of mucosal antibodies to Mcat proteins OMP CD (IgG, P < 0.0001), OppA (IgG, P = 0.018), Hag (IgG and IgA, both P < 0.0001), and PilA2 (IgA, P < 0.0001) was lower in sOP than NOP children. Higher levels of mucosal IgG to Hag (P = 0.039) and PilA2 (P = 0.0076), and IgA to OMP CD (P = 0.010), OppA (P = 0.030), and PilA2 (P = 0.043) were associated with lower carriage of Mcat in NOP but not sOP children. Higher levels of mucosal IgG to OMP CD (P = 0.0070) and Hag (P = 0.0003), and IgA to Hag (P = 0.0067) at asymptomatic colonization than those at onset of AOM were associated with significantly lower rate of Mcat NP colonization progressing to AOM in NOP compared to sOP children (3% vs. 26%, P < 0.0001). In conclusion, sOP children had a diminished mucosal antibody response to Mcat proteins, which was associated with higher frequencies of asymptomatic NP colonization and NP colonization progressing to Mcat-caused AOM. Enhancing Mcat antigen-specific mucosal immune responses to levels higher than achieved by natural exposure will be necessary to prevent AOM in sOP children.